Heterozygous premature termination in zinc-finger domain of Krüppel-like factor 2 gene associates with dysregulated immunity - Pernaa, Nora; Keskitalo, Salla; Chowdhury, Iftekhar; Nissinen, Antti; Glumoff, Virpi; Keski-Filppula, Riikka; Junttila, Juhani; Eklund, Kari K.; Santaniemi, Wenny; Siitonen, Sanna; Seppänen, Mikko RJ.; Vähäsalo, Paula; et al. (Frontiers in Immunology, 2022)
Kruppel-like factor 2 (KLF2) is a transcription factor with significant roles in development, maturation, differentiation, and proliferation of several cell types. In immune cells, KLF2 regulates maturation and trafficking of lymphocytes and monocytes. KLF2 participates in regulation of the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) pathway. Although pulmonary arterial hypertension (PAH) related to KLF2 deficiency has been suggested, genetic KLF2 deficiency associated with immune dysregulation has not been described. We identified a family whose members suffered from lymphopenia, autoimmunity, and malignancy. Whole exome sequencing revealed a KLF2 p.(Glu318Argfs*87) mutation disrupting the highly conserved zinc finger domain. We show a reduced amount of KLF2 protein, defective nuclear localization and altered protein-protein interactome. The phenotypically variable positive cases presented with B and T cell lymphopenia and abnormalities in B and T cell maturation including low naive T cell counts and low CD27+IgD-IgM- switched memory B cells. KLF2 target gene (CD62L) expression was affected. Although the percentage of (CD25+FOXP3+, CD25+CD127-) regulatory T cells (Treg) was high, the naive Treg cells (CD45RA+) were absent. Serum IgG1 levels were low and findings in one case were consistent with common variable immunodeficiency (CVID). Transcription of NF-κΒ pathway genes and p65/RelA phosphorylation were not significantly affected. Inflammasome activity, transcription of genes related with JAK/STAT pathway and interferon signature were also comparable to controls. Evidence of PAH was not found. In conclusion, KLF2 deficiency may be associated with familial immune dysregulation. Although the KLF2 deficient family members in our study suffered from lymphopenia, autoimmunity or malignancy, additional study cohorts are required to confirm our observations.